Polyurethane composite material for aluminum-plastic film of new energy automobile battery
By adding specific components to the polyurethane composite material and adjusting the component distribution ratio, the problem of insufficient heat resistance and wear resistance of the material in the aluminum-plastic film of new energy vehicle batteries is solved, and the efficient performance of the material is improved and the service life is extended.
Patent Information
- Application Number
- CN202411841568.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-25
AI Technical Summary
The existing polyurethane composite materials lack high heat resistance and high wear resistance in aluminum-plastic films of new energy vehicle batteries, resulting in a short service life.
The composition ratio of the material is adjusted by adding wollastonite, calcium carbonate, polyethylene particles, plasticizers, antioxidants, ultraviolet absorbers and hydrophobic agents to the polyurethane composite material to improve the heat resistance, wear resistance and ultraviolet resistance of the material.
It achieves high heat resistance and wear resistance of polyurethane composite materials, extends service life and improves the overall performance of the material.
Smart Images

Figure BDA0005188085610000071 
Figure BDA0005188085610000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a polyurethane composite material for aluminum-plastic films of new energy vehicle batteries. Background Art
[0002] Polyurethane composite materials are mainly used as one of the core packaging materials in battery aluminum-plastic films, located between aluminum foil and other protective layers. Its main function is to provide flexibility, sealing, mechanical strength and electrical insulation, and protect the battery from external environmental influences. Usually, polyurethane composite materials will act as buffers and supports in the inner or outer layers of the film to ensure that the battery is not damaged during operation and enhance its durability and safety.
[0003] The application of polyurethane composite materials in battery aluminum-plastic films has achieved good results, but with the continuous development of new energy vehicle battery technology, the requirements for battery membranes are getting higher and higher. Therefore, it is an urgent problem to produce a polyurethane composite material that can be applied to automotive battery aluminum-plastic films and has high heat resistance, high wear resistance and long service life. Summary of the invention
[0004] The main purpose of the present invention is to provide a polyurethane composite material for aluminum-plastic film of new energy vehicle batteries, which can effectively solve the problems in the background technology.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A polyurethane composite material for aluminum-plastic film of new energy vehicle batteries comprises the following components in parts by weight: 25-50 parts of toluene diisocyanate, 25-50 parts of diphenylmethane diisocyanate, 50-75 parts of polyether diol, 2-8 parts of wollastonite, 2-8 parts of calcium carbonate, 5-9 parts of polyethylene particles, 10-15 parts of plasticizer, 3-7 parts of antioxidant, 2-6 parts of ultraviolet absorber and 4-10 parts of hydrophobic agent.
[0007] Preferably, the composition comprises the following components in parts by weight: 35 parts of toluene diisocyanate, 42 parts of diphenylmethane diisocyanate, 59 parts of polyether diol, 6 parts of wollastonite, 5 parts of calcium carbonate, 6 parts of polyethylene particles, 12 parts of plasticizer, 5 parts of antioxidant, 3 parts of ultraviolet absorber and 7 parts of hydrophobic agent.
[0008] Preferably, the plasticizer is any one of phthalate esters or fatty acid esters.
[0009] Preferably, the antioxidant is any one of tert-butylhydroquinone, dialkyltriphenylphosphine, and zinc sulfide, or a combination of several of them.
[0010] Preferably, the ultraviolet absorber includes titanium dioxide and zinc oxide, and the usage ratio of titanium dioxide to zinc oxide is 1:1.
[0011] Preferably, the hydrophobic agent is any one of aminosilane, phenylsilane and fluorosilane or a combination of several of them.
[0012] The present invention also discloses the application of the polyurethane composite material in the aluminum-plastic film of the new energy vehicle battery. The polyurethane composite material is arranged as a functional layer between the outer layer of the aluminum-plastic film of the new energy battery and the aluminum foil layer.
[0013] The present invention also discloses a method for preparing the polyurethane composite material, and the specific steps are as follows:
[0014] S1. Accurately weigh each component;
[0015] S2, putting polyether diol into a reaction kettle, heating to 60-80°C and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, reacting for 2-3 hours to obtain a polyurethane prepolymer;
[0016] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0017] S4, then add plasticizer, antioxidant, ultraviolet absorber and hydrophobic agent in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention adds wollastonite and calcium carbonate to the polyurethane composite material, which can control the production cost and improve the wear resistance and heat resistance of the material to a certain extent, and improve the hardness and rigidity of the material.
[0020] 2. The present invention adds polyethylene particles to the polyurethane composite material, uses the polyethylene particles as an organic filler, and controls the heating ratio to adjust the fluidity of the polyurethane composite material and enhance the wear resistance of the polyurethane composite material to a certain extent.
[0021] 3. The present invention can increase the flexibility of polyurethane by adding plasticizers, antioxidants, ultraviolet absorbers and hydrophobic agents to the polyurethane composite material, prevent the polyurethane composite material from deteriorating due to oxidation during use, extend the service life, improve the ultraviolet resistance of the polyurethane composite material, and avoid aging and embrittlement of the material. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] The invention discloses a polyurethane composite material. Specifically, the material is specially used for aluminum-plastic film of new energy vehicle batteries. Furthermore, the material is arranged as a functional layer between the outer layer of the aluminum-plastic film of the new energy battery and the aluminum foil layer. The main function of the material is to provide flexibility, sealing, mechanical strength and electrical insulation, protect the battery from the influence of the external environment, act as a buffer and support, ensure that the battery is not damaged during operation, and enhance its durability and safety.
[0024] In the present invention, the raw materials used in the polyurethane composite material include toluene diisocyanate, diphenylmethane diisocyanate, polyether diol, wollastonite, calcium carbonate, polyethylene particles, plasticizer, antioxidant, ultraviolet absorber, and hydrophobic agent;
[0025] Among them, the plasticizer is any one of phthalate or fatty acid ester; the antioxidant is any one of tert-butylhydroquinone, dialkyltriphenylphosphine, zinc sulfide or a combination of several; the ultraviolet absorber includes titanium dioxide and zinc oxide, and the dosage ratio of titanium dioxide and zinc oxide is 1:1; the hydrophobic agent is any one of aminosilane, phenylsilane and fluorosilane or a combination of several.
[0026] The following is a detailed description with reference to specific embodiments:
[0027] Example 1
[0028] In this embodiment, the polyurethane composite material is prepared according to the following steps:
[0029] S1. Accurately weigh the following components: 25 parts of toluene diisocyanate, 25 parts of diphenylmethane diisocyanate, 50 parts of polyether diol, 2 parts of wollastonite, 2 parts of calcium carbonate, 5 parts of polyethylene particles, 10 parts of phthalate, 3 parts of zinc sulfide, 1 part of titanium dioxide, 1 part of zinc oxide, and 4 parts of aminosilane.
[0030] S2, putting polyether diol into a reaction kettle, heating to 70° C. and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, and reacting for 2 hours to obtain a polyurethane prepolymer;
[0031] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0032] S4, then add phthalate, zinc sulfide, titanium dioxide, zinc oxide and aminosilane in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0033] Example 2
[0034] In this embodiment, the polyurethane composite material is prepared according to the following steps:
[0035] S1. Accurately weigh the following components: 29 parts of toluene diisocyanate, 39 parts of diphenylmethane diisocyanate, 60 parts of polyether diol, 4 parts of wollastonite, 4 parts of calcium carbonate, 6 parts of polyethylene particles, 12 parts of phthalate, 3 parts of dialkyltriphenylphosphine, 2 parts of titanium dioxide, 2 parts of zinc oxide, and 5 parts of aminosilane;
[0036] S2, putting polyether diol into a reaction kettle, heating to 70° C. and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, and reacting for 2 hours to obtain a polyurethane prepolymer;
[0037] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0038] S4, then add phthalate, divinyl triphenylphosphine, titanium dioxide, zinc oxide and aminosilane in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0039] Example 3
[0040] In this embodiment, the polyurethane composite material is prepared according to the following steps:
[0041] S1. Accurately weigh the following components: 35 parts of toluene diisocyanate, 42 parts of diphenylmethane diisocyanate, 59 parts of polyether diol, 6 parts of wollastonite, 5 parts of calcium carbonate, 6 parts of polyethylene particles, 12 parts of phthalate, 5 parts of dialkyltriphenylphosphine, 1.5 parts of titanium dioxide, 1.5 parts of zinc oxide, and 7 parts of aminosilane;
[0042] S2, putting polyether diol into a reaction kettle, heating to 70° C. and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, and reacting for 2 hours to obtain a polyurethane prepolymer;
[0043] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0044] S4, then add phthalate, divinyl triphenylphosphine, titanium dioxide, zinc oxide and aminosilane in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0045] Example 4
[0046] In this embodiment, the polyurethane composite material is prepared according to the following steps:
[0047] S1. Accurately weigh the following components: 45 parts of toluene diisocyanate, 45 parts of diphenylmethane diisocyanate, 70 parts of polyether diol, 7 parts of wollastonite, 6 parts of calcium carbonate, 7 parts of polyethylene particles, 14 parts of phthalate, 6 parts of tert-butylhydroquinone, 2.5 parts of titanium dioxide, 2.5 parts of zinc oxide, and 9 parts of aminosilane.
[0048] S2, putting polyether diol into a reaction kettle, heating to 70° C. and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, and reacting for 2 hours to obtain a polyurethane prepolymer;
[0049] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0050] S4, then add phthalate, tert-butylhydroquinone, titanium dioxide, zinc oxide and aminosilane in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0051] Example 5
[0052] In this embodiment, the polyurethane composite material is prepared according to the following steps:
[0053] S1. Accurately weigh the following components: 50 parts of toluene diisocyanate, 50 parts of diphenylmethane diisocyanate, 75 parts of polyether diol, 8 parts of wollastonite, 8 parts of calcium carbonate, 9 parts of polyethylene particles, 15 parts of phthalate, 7 parts of tert-butylhydroquinone, 3 parts of titanium dioxide, 3 parts of zinc oxide, and 10 parts of aminosilane;
[0054] S2, putting polyether diol into a reaction kettle, heating to 70° C. and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, and reacting for 2 hours to obtain a polyurethane prepolymer;
[0055] S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly;
[0056] S4, then add phthalate, tert-butylhydroquinone, titanium dioxide, zinc oxide and aminosilane in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.
[0057] Take equal amounts of the polyurethane composite materials prepared in Examples 1-5, and prepare lithium battery aluminum-plastic films respectively according to the following steps:
[0058] Step 1: Select an aluminum foil with a thickness of 15 μm, and coat the surface of the aluminum foil with polyolefin to form a 10 μm polyolefin layer on the surface of the aluminum foil;
[0059] Step 2: Take the polyurethane composite materials prepared in Examples 1-5 respectively, heat and melt them, and evenly coat them on the surface of the polyolefin layer in the step to form a thickness of 12 μm, and cure them by ultraviolet irradiation to form a polyurethane functional layer;
[0060] Step 3: The semi-finished product obtained in step 2 is heat-sealed with polyolefin to form a heat-sealing layer with a thickness of 10 μm, thereby obtaining a new energy vehicle lithium battery aluminum-plastic film test sample.
[0061] The aluminum-plastic films for lithium batteries of new energy vehicles prepared by using the polyurethane composite materials prepared in Examples 1-5 in the above steps were subjected to the following performance tests, as follows:
[0062] 1. Drawing depth performance test
[0063] A 120*100mm deep drawing die with an R angle of 3.5° was used for stamping at a speed of 6mm / sec. After stamping, the appearance of the sample was checked and the limit drawing depth was measured. The test results are shown in Table 1 below.
[0064] 2. Puncture performance test
[0065] The aluminum-plastic film samples were cut into 100*100mm samples, and the universal tensile testing machine was used in compression mode, with a needle diameter of 1mm and a pressing speed of 50mm / min, and the pressing force when the sample was punctured was recorded. The test results are shown in Table 1 below.
[0066] 3. Tensile modulus test
[0067] The samples were cut into 15*15mm pieces and subjected to stress-strain tests. The test results are shown in Table 2 below.
[0068] 4. Antioxidant performance test
[0069] The samples were cut into 100*100㎜ specimens and placed in a sealed container with an oxygen content of 50% and a humidity of 80%. The surface of the aluminum-plastic film was observed to see if there was any color change, and the time required for the color change to occur was recorded. The results are shown in Table 3 below.
[0070] Table 1: Results of deep punching performance test and puncture performance test in Examples 1-5
[0071] sample Limit punching depth / mm Puncture force value / N Example 1 7.0 30 Example 2 7.5 35 Example 3 7.3 34 Example 4 7.2 32 Example 5 7.0 25
[0072] It can be seen from Table 1 above that the polyurethane composite materials prepared by the present invention have good strength and puncture resistance when used in aluminum-plastic films of lithium batteries for new energy vehicles, especially the ratio of the components in Example 2, which has a better effect.
[0073] Table 2: Test results of single-layer stretched film of Examples 1-5
[0074] Example 1 Example 2 Example 3 Example 4 Example 5 Tensile strength / MPa 320 335 329 327 309
[0075] It can be seen from Table 2 above that when the polyurethane composite material prepared by the present invention is used in the aluminum-plastic film of new energy vehicle lithium battery, its overall tensile strength is strong. Under normal circumstances, the tensile strength of the aluminum-plastic film of new energy vehicle lithium battery is generally between 70-150MPa. The sample prepared in this application, especially in Example 2, is far superior to commercially available products.
[0076] Table 3: Antioxidant performance test results of Examples 1-5
[0077]
[0078]
[0079] It can be seen from Table 3 above that when the polyurethane composite material prepared by the present invention is used in the aluminum-plastic film of lithium batteries for new energy vehicles, by adding titanium dioxide and zinc oxide as ultraviolet absorbers and any one or more of tert-butylhydroquinone, dialkyltriphenylphosphine, and zinc sulfide as antioxidants, the overall product has strong antioxidant properties.
[0080] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A polyurethane composite material, characterized in that: The composition comprises the following components in parts by weight: 25-50 parts of toluene diisocyanate, 25-50 parts of diphenylmethane diisocyanate, 50-75 parts of polyether diol, 2-8 parts of wollastonite, 2-8 parts of calcium carbonate, 5-9 parts of polyethylene particles, 10-15 parts of plasticizer, 3-7 parts of antioxidant, 2-6 parts of ultraviolet absorber and 4-10 parts of hydrophobic agent.
2. A polyurethane composite material according to claim 1, characterized in that: The composition comprises the following components in parts by weight: 35 parts of toluene diisocyanate, 42 parts of diphenylmethane diisocyanate, 59 parts of polyether diol, 6 parts of wollastonite, 5 parts of calcium carbonate, 6 parts of polyethylene particles, 12 parts of plasticizer, 5 parts of antioxidant, 3 parts of ultraviolet absorber and 7 parts of hydrophobic agent.
3. The polyurethane composite material according to claim 1, characterized in that: The plasticizer is any one of phthalate esters or fatty acid esters.
4. The polyurethane composite material according to claim 1, characterized in that: The antioxidant is any one of tert-butylhydroquinone, di-alkenyl triphenylphosphine and zinc sulfide or a combination of several of them.
5. The polyurethane composite material according to claim 1, characterized in that: The ultraviolet absorber includes titanium dioxide and zinc oxide, and the usage ratio of titanium dioxide to zinc oxide is 1:
1.
6. The polyurethane composite material according to claim 1, characterized in that: The hydrophobic agent is any one of aminosilane, phenylsilane and fluorosilane or a combination of several of them.
7. Application of the polyurethane composite material according to any one of claims 1 to 6 in aluminum-plastic film for new energy vehicle batteries, characterized in that: The polyurethane composite material is arranged as a functional layer between the outer layer of the aluminum-plastic film and the aluminum foil layer of the new energy battery.
8. A method for preparing the polyurethane composite material according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: S1. Accurately weigh each component; S2, putting polyether diol into a reaction kettle, heating to 60-80°C and starting stirring, then adding toluene diisocyanate and diphenylmethane diisocyanate, reacting for 2-3 hours to obtain a polyurethane prepolymer; S3, adding wollastonite, calcium carbonate and polyethylene particles to the polyurethane prepolymer in sequence, and stirring at a constant speed to mix evenly; S4, then add plasticizer, antioxidant, ultraviolet absorber and hydrophobic agent in sequence, mix thoroughly and evenly, and then cool and solidify naturally to obtain the polyurethane composite material.